2017
DOI: 10.1080/00909882.2017.1320569
|View full text |Cite
|
Sign up to set email alerts
|

A theater intervention to promote communication and disclosure of suicidal ideation

Abstract: Young adults from Montana have a higher rate of suicide than their national counterparts. There is a clear need for targeted interventions to address this disparity. The authors evaluate a community-based, narrative theater project designed to increase awareness and use of suicide prevention resources among eastern Montana youth. As a first step, seven group interviews with Montana young adults (n = 27) were conducted to identify current perceptions about suicide and suicide prevention. Interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 41 publications
(65 reference statements)
0
26
0
Order By: Relevance
“…They may also feel better understood and less lonely; talking may also help them to structure thoughts [ 37 ]. Assuming that talking is beneficial, direct and personal forms of influence are needed to reach those individuals experiencing suicidal ideation in need of help [ 18 ]. For instance, the intervention ‘Life Goals’ aims to increase the participation of people who are socially vulnerable by means of sporting activities, and may encourage participants to openly discuss suicidal thoughts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also feel better understood and less lonely; talking may also help them to structure thoughts [ 37 ]. Assuming that talking is beneficial, direct and personal forms of influence are needed to reach those individuals experiencing suicidal ideation in need of help [ 18 ]. For instance, the intervention ‘Life Goals’ aims to increase the participation of people who are socially vulnerable by means of sporting activities, and may encourage participants to openly discuss suicidal thoughts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no studies have assessed which factors are related to non-disclosure of suicidal ideation in the general population, while empirical evidence about the prevalence is also scarce. Knowledge and understanding of this subject are important as the disclosure of suicidal ideation is often seen as a crucial first step in the help-seeking process [ 18 ]. Therefore, the current study aims to gain insight into factors that are associated with non-disclosure of suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…The Let’s Talk program directors hosted and facilitated a theatre workshop to address the risk of suicide (Keller, Austin & McNeill, 2017). Each writer-actor group met bi-weekly for 12 weeks to share their personal experiences with suicide and/or major depression, and to collaboratively write a unique play based on their experiences.…”
Section: A Community-based Theatre Approach To Preventing Suicidementioning
confidence: 99%
“…Lalonde, discussing Indigenous First Nations Canadians, describes this as “…the special circumstance of finding oneself tugged by both enculturative and acculturative currents” [20] (p. 139). At present, many NA communities in Montana lack sufficient social, emotional, and financial resources, which may increase suicidal behavior risks [21,22]. Nationwide, Indigenous youth are 2.5 times more likely to experience suicidal ideation or attempts than youth from other racial/ethnic youth groups [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that suicide rates are greater in rural areas than in urban areas [45,46,47,48,49]. When mental illness is combined with low social and/or economic resources, stigma levels (self-stigma and community stigma) contribute to suicidal ideation through factors such as social isolation, hopelessness, and a perception of thwarted belongingness or being a burden [19,22]. Meta-analyses of quantitative and qualitative studies confirm that stigma has a negative effect on help-seeking, thus supporting the idea that stigma-reduction programs require a nuanced approach [8] to meet each unique community’s needs.…”
Section: Introductionmentioning
confidence: 99%